Potential Drug Interactions in Inpatients with Chronic Kidney Disease at Undata Hospital, Palu City, Indonesia (Sciences of Pharmacy, 2023)
Patients with Chronic Kidney Disease (CKD) often receive a combination of medications, which can have beneficial effects but may also lead to ineffective treatment. The objective of this study was to analyze potential drug interactions in CKD patients admitted to the Seroja ward at Undata Hospital in Palu, Central Sulawesi Province, during the year 2022. The study was conducted prospectively from July 20 to September 18, 2022, involving a total of 40 patients. The research utilized a non-experimental observational design, and the results were presented descriptively using purposive sampling based on predefined criteria. Drug interaction were screened using the Drug Interaction Checker tool. The study revealed that among CKD patients, a higher percentage of men (55%) than women (44%) were observed, with the highest percentage in the age group of 46–55 (27.5%). The most commonly drug group used was loop diuretics and furosemide (18.75%). The most significant potential drug interactions were pharmacodynamic interactions (12.5% in 5 cases) with minor significance, followed by pharmacokinetic interactions (2.5% in 1 case) with major significance, particularly in the use of calcium channel blockers (CCBs) and statins. Based on the findings, minor interaction cases do not always yield negative outcomes. In certain clinical practices, these interactions are intentionally utilized to achieve favorable results. Instances of major interactions with drug use should be avoided, and alternative drugs should be considered. In urgent situations where the drug is necessary, restrictions can be applied, and close monitoring of the patient's clinical status is vital.